Tranexamic acid in ear surgery: enhancing surgical field visibility and reducing bleeding—a systematic review and meta analysis - Sung Ryul Shim; Jieun Shin; Cheol Mog Hwang; Yong Kyun Kim; Jong Bum Park; Jong-Yeup Kim (Scientific Reports)
Abstract Ear surgeries such as mastoidectomy require a clear surgical field with minimal bleeding for optimal visualization and outcomes. However, bleeding during these microscopic and endoscopic procedures can obscure the surgeon’s view and potentially impact surgical precision and efficiency. The study aimed to identify the effect of intravenous tranexamic acid during ear surgery. PubMed/MEDLINE, Cochrane Library, and Embase were systematically searched from inception through August 31, 2024. Two authors also manually and independently searched all relevant studies. We included RCTs with (1) patients diagnosed with otitis media or middle ear infection; (2) interventions included intravenous tranexamic acid during ear surgery as mastoidectomy; (3) comparisons were specified as normal saline or no treatment; and (4) outcomes were subjective score (bleeding score and surgeon satisfaction), and objective markers (amount of bleeding, duration of surgery, and mean arterial pressure [MAP]). Data extraction was completed independently by 2 extractors and cross-checked for research integrity. The pairwise meta-analysis was performed to compare the treatment group with control used in ear surgery. Hedges’ g standardized mean differences (SMDs) and mean difference (MD) were used for improvement in all outcomes. Efficacy outcomes included subjective scores as bleeding score and surgeon satisfaction, as well as objective markers measuring amount of bleeding, duration of surgery, and MAP. A comprehensive literature search was conducted which identified 4 RCTs with 248 patients. In subjective score, the pooled SMD 3.871 (95% CI 0.508, 7.234) for surgeon satisfaction between treatments for controls was significantly increased. In objective markers, the pooled MD for amount of bleeding and MAP were − 28.484 ml (95% CI − 35.785, − 21.182) and − 2.874 mmHg (95% CI − 4.732, − 1.015), indicating that the intravenous tranexamic acid during ear surgery significantly reduced amount of bleeding and MAP. The findings of this meta-analysis indicate that intravenous tranexamic acid can be an effective method for reducing bleeding during ear surgery. This is achieved by significantly improving the surgical field of view and lowering MAP.